(untitled) (Docentes 2.0 Journal, 2025)
Educational quality in public institutions depends on effective teacher support strategies to improve pedagogical practices. In Peru, the quality of support presents deficiencies that negatively impact teachers’ performance. The present study aimed to analyze the strengthening of pedagogical practices in public institutions through contextualized teacher support. It was framed in the positivist paradigm, hypothetical-deductive method, and quantitative approach with a non-experimental descriptive-correlational design. The sample consisted of 120 teachers from a district of Lima, Peru. Two questionnaires evaluated pedagogical support and practice variables, with reliabilities of 0.864 and 0.851. Spearman’s Rho correlation test was used to evaluate the association between the variables. The results revealed a positive and significant correlation (Rho = 0.670**), indicating that greater pedagogical support is associated with strengthening teaching practices. Strategies such as refresher workshops, classroom visits, and interlearning groups showed differentiated impacts, with collaborative workshops and groups being the most effective. Collaborative learning, support quality, teacher retention, support style, and reflective practice are important factors in support effectiveness. These findings highlight the relevance of pedagogical support in the professional improvement of teachers, suggesting the implementation of continuing education programs and comprehensive approaches that promote reflection and the development of practical skills, contributing to the strengthening of educational quality.